2016
DOI: 10.1007/s13410-016-0511-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictive risk modelling for early hospital readmission of patients with diabetes in India

Abstract: Hospital readmission is an important contributor to total medical expenditure and is an emerging indicator of quality of care. The goal of this study is to analyze key factors using machine learning methods and patients' medical records of a reputed Indian hospital which impact the all-purpose readmission of a patient with diabetes and compare different classification models that predict readmission and evaluate the best model. This study classified the patients into two different risk groups of readmission (Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…One of the first predictive modeling of hospital readmissions using healthcare data from Quebec, Canada by Hosseinzadeh et.al 16 showed that Naïve Bayes models (0.65) performed better than Random Forest models (0.64). Using a diabetes cohort from a hospital in India, Duggal et.al 17 showed that Naïve Bayes (0.67) showed higher readmission associated savings compared to logistic regression (0.67), Random Forests (0.68), Adaboost (0.67) and Neural Networks (0.62). Futoma et.al 30 showed that Random Forests (0.68) and deep learning using neural networks (0.67) have similar accuracy rate with >1 million patients and > 3 million admission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first predictive modeling of hospital readmissions using healthcare data from Quebec, Canada by Hosseinzadeh et.al 16 showed that Naïve Bayes models (0.65) performed better than Random Forest models (0.64). Using a diabetes cohort from a hospital in India, Duggal et.al 17 showed that Naïve Bayes (0.67) showed higher readmission associated savings compared to logistic regression (0.67), Random Forests (0.68), Adaboost (0.67) and Neural Networks (0.62). Futoma et.al 30 showed that Random Forests (0.68) and deep learning using neural networks (0.67) have similar accuracy rate with >1 million patients and > 3 million admission.…”
Section: Resultsmentioning
confidence: 99%
“…There is an immediate need for tools that may be used at the bedside or as part of discharge disposition planning to assess and minimize risk for readmission. Studies led by Hosseinzadeh et.al 16 leverage claims data to predict all-cause readmissions, and Duggal et.al 17 used EMR-derived clinical and administrative data to predict readmission in the setting of a diabetes cohort. To the best of our knowledge, our study is one of the first attempts to use phenome-wide data to identify novel factors driving readmissions related to congestive heart failure and develop EMR-wide prediction models with orthogonal validation to predict the readmission event.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it could be subjected to predictive modeling using neural network methods. In the current issue, Duggal et al used machine learning methods to predict readmission of patients who were discharged from a hospital [4]. From 9381 records, random forest was the optimal classifier using area under precision-recall curve to identify risk factors.…”
mentioning
confidence: 99%
“…The earliest applications of NLP is medical domain [10]. Recent researches uses Apache cTAKES to annotate unstructured EHR [11].…”
Section: IImentioning
confidence: 99%